Perkembangan Moral Dan Disiplin Positif Pada Anak Usia Dini - Meri Lusia Anggraini; Zusy Ariyanti; Dwi Enggal Wahyuni (ALMURTAJA: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Moral development and positive discipline are important aspects of early childhood education as they serve as the foundation for character formation, social behavior, and children's ability to understand and apply values in their daily lives. However, the development of children's morality and discipline continues to face various challenges influenced by parenting styles, family environments, school settings, and social changes in society. This study aims to systematically review previous research on moral development and positive discipline in early childhood, analyze effective positive discipline strategies according to children's stages of moral development, and identify research gaps that can serve as a basis for future studies and educational practices in early childhood education. This study employed a Systematic Literature Review (SLR) method by analyzing 30 relevant scientific articles. Data were collected through the processes of identification, selection, analysis, and synthesis of articles that matched the research focus. The findings indicate that positive discipline is effective in fostering children's moral character through habituation, role modeling, positive communication, and reinforcement of desirable behaviors. Furthermore, parental and teacher role modeling, democratic parenting styles, and collaboration between families and schools were found to be crucial factors in supporting children's moral development and positive discipline. The review also revealed that studies examining the influence of digital technology and family-school collaboration models on children's moral development remain limited. Therefore, the consistent and collaborative implementation of positive discipline can serve as an effective strategy for promoting moral development and character building in early childhood.